Development of Android-Based Learning Media for High School Students in Indonesia: A Systematic Review of Literature - Yohanis Ndapa Deda; Hermina Disnawati; Otaget Daniel; Rooselyna Ekawati (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
This study aims to comprehensively examine research on developing android-based learning media(ABLM) in Indonesia from 2015 to 2022. The research method used is the SLR to explore 32 articles from the accreted journals Sinta 1 and Sinta 2 by the Kemristekdikti RI with the keyword "Android" from 2015 to 2022. The results show that the trend of ABLM development research in Indonesia in the last eight years has continued to increase. The ADDIE model has been the most widely used research and development (RnD) method over the previous eight years. The questionnaire is the most dominant data collection tool used in Indonesia. The most researched subject related to research on developing ABLM in Indonesia is chemistry. The Indonesian Science Education Journal is the journal that has contributed the most to publishing ABLM development articles. The theory used in ABLM development research is problem-solving, critical thinking, and self-diagnosis skills. The study indicates that ABLM influences problem-solving (PS) abilities, critical thinking, and self-diagnosis. Meanwhile, a brief outline of the ABLM procedure for development for further study was presented in this paper Keywords: Developing Learning Media, Android-Based Learning, Learning Media